Realized impact of COVID‐19 related disruptions on the National Bowel Cancer Screening Program - Irwin, Matthew P.; Dutta, Trisha; Jambor, Maxwell A.; Morgan, Matthew J.; Turner, Catherine E.; Liang, Yicong (ANZ journal of surgery, 2024)
Background Colorectal cancer is the second most common cause of cancer mortality in Australia (1). The National Bowel Cancer Screening Program (NBCSP) aims to reduce mortality through early detection with a biennial faecal occult blood test for Australians aged 50–74 years (2). Modelling predicted COVID‐19 would reduce participation and delay colonoscopies despite the NBCSP continuing during the pandemic (3). This study analyses the realized impact of COVID‐19 related disruptions on the NBCSP and the effect on mortality. Methods NBCSP participation, time to colonoscopy and annualized mortality were compared before and during COVID‐19. The effect on mortality was determined using a validated microsimulation model (4, 5). Results From 1 January 2018 to 31 December 2019, 2 497 317 people participated in the NBCSP and 168 390 received a colonoscopy, compared to 2 490 265 and 162 573 from 1 January 2020 to 31 December 2021. Relative participation decreased 6 % and the proportion of colonoscopies performed within the recommended 120 days increased 14.5%. A disproportionally greater impact was observed outside major cities and in lower socioeconomic areas. An estimated 98–111 additional colorectal cancer deaths resulted from 3 % fewer colonoscopies performed during the pandemic. Conclusion This study presents the most comprehensive analysis of the realized impact of COVID‐19 on the NBCSP. Catch‐up screening would be best targeted at Australians from rural and lower socioeconomic areas where participation remains low. Streamlined referral pathways and additional colonoscopy provisioning is required as less than two thirds of screen positive patients receive a colonoscopy within the recommended 120 days. Colorectal cancer is a common cause of cancer mortality, and the National Bowel Cancer Screening Program aims to reduce this. This study compares the impact of COVID‐19 with modelling that predicted reduced participation and delayed colonoscopies. During the pandemic, relative participation decreased six percent, the proportion of colonoscopies performed within the recommended 120 days increased 14.5%, and there were an estimated 98‐111 additional colorectal cancer deaths resulting from three percent fewer colonoscopies.